A Simple Nudge Increases Socioeconomic Diversity in Undergraduate Economics - Todd Pugatch; Elizabeth Schroeder (Global Labor Organization (GLO), 2021)
We assess whether a light-touch intervention can increase socioeconomic and racial diversity in undergraduate Economics. We randomly assigned over 2,200 students a message with basic information about the Economics major; the basic message combined with an emphasis on the rewarding careers or financial returns associated with the major; or no message. Messages increased the proportion of first generation and underrepresented minority (URM) students majoring in Economics by five percentage points. This effect size was sufficient to reverse the gap in Economics majors between first generation/URM students and students not in these groups. Effect sizes were larger and more precise for better-performing students and first generation students. Extrapolating to the full sample, the treatment would double the proportion of first generation and underrepresented minority students majoring in Economics.
Keywords: I21; I23; 330; college major choice; diversity in Economics; higher education; nudges; randomized control trial